TO THE LIGHTHOUSE E THE WAVES ENTRE A MEMÓRIA E O PICTÓRICO - Gelinski, Rosana de Fátima (2013)
Virginia Woolf is considered one of the most important British writers. Besides showing in her texts an enormous concern with breaking the limit space-time, she engaged in a process of literary experimentation in order to represent the objective and subjective reality of the invented subjects. Discuss the construction of memory-images and how it is re-signified in the opuses To The Lighthouse (1927) and The Waves (1931) by Virginia Woolf is the main interest of this dissertation, which starts from the assumption that everything begins in the memory and ends in the image. As noted Filloux (1959, p.122): "for a reminder to reappear in consciousness, it has to come down from the heights of the memory to the moment where the action takes place." This action, as evidenced in the interior life of the characters in both narratives, has a perceptual bias that is realized in the image. At first, the paper discusses about the different conceptions of the memorialistic universe, considering its intrinsic relationship with time and space. Next, it explores the woolfian language and its proximity to impressionism/Post-Impressionism, and only then makes a more fruitful analysis of the image represented not only in memory of the characters, but in the Woolfian narrative itself. In order to achieve the objectives of this study, the research is supported mainly on the bibliography of Henri Bergson (2006), once its concepts enable greater understanding of the constitution of memory-images. Placed that woolfian narratives configure themselves into a true poetics of space, this paper also supports itself on some propositions of Gaston Bachelard (2008), in particular those exploring the creative imagination. On the pictorial questions, the work privileges, among other authors, the impressionist concepts by Meyer Schapiro (2002). The way Virginia Woolf represents the psychological universe of her characters, as well as the simultaneity between the interior and exterior, which are remarkable in their literary style, lead us to think that all recollection conducts itself to a type of pictorial construct, that is, the images constructed in the narratives from the stream of consciousness can be viewed as if they were literally framed. Thus, both the novels discussed here show that literature influenced by the Impressionist aesthetic implies a new way to view pictures.